A randomised, controlled, crossover study to investigate the safety and response of 1R, 2S‐methoxamine hydrochloride (NRL001) on anal function in healthy volunteers. (March 2014) - Simpson, J. A. D.; Bush, D.; Gruss, H. J.; Jacobs, A.; Pediconi, C.; Scholefield, J. H.
Abstract: Aims: This study aimed to assess the dose and volume effects of suppository preparations and safety of NRL001 (one of four possible stereoisomers of methoxamine hydrochloride) on anal sphincter tone using rectal suppositories in healthy adult volunteers. Methods: This was a Phase I, single‐centre, randomised, double‐blind, three‐way crossover study during which subjects received three single doses of 1 g rectal suppositories (containing 5 or 10 mg NRL001 or matching placebo) or 2 g rectal suppositories (containing 10 or 15 mg NRL001 or matching placebo) on three separate dosing days. The outcome measures were mean anal resting pressure (MARP) variables (monitored continuously for 20–30 min before and up to 6 h after dosing), pharmacokinetics (PK) and safety assessments. Results: Twenty‐six subjects were dosed with study medication. Two subjects were withdrawn prematurely and were not included in the main analysis. There was a dose‐dependent increase in anal sphincter tone (MARP) when comparing the 5 and 10 mg doses of NRL001; however, the 15 mg dose did not have a significantly greater effect than the 10 mg dose. Suppository size (1 or 2 g) did not appear to have an effect on sphincter tone. There was no evidence against dose proportionality for the PK variables, but the mean maximum plasma concentration ( C max ) for the 1 g suppository group was higher than for the 2 g group. Twenty‐one adverse events were reported in 8 (30.8%) subjects. A dose dependent decrease in heart rate was noted; however, there were no adverse events reported that were related to this reduction in heart rate. Conclusions: The increase in anal sphincter tone supports the potential therapeutic use of NRL001 in treating faecal incontinence, with further studies in patients required. NRL001 was well tolerated in single doses of up to 15 mg.